Sosilisasi Pencegahan Bullying di MI At-Taqwa Desa Gandasoli Kecamatan Tanjung Siang Kabupaten Subang - Fachmi Fachrurrozi; Afif Nurseha; Siti Sholihah; Windah Awaliah (P3M FIA UNKRIS, 2026)
Bullying remains one of the most common social problems in elementary school environments and can negatively affect students’ emotional well-being, self-confidence, social relationships, and learning processes. Preventive efforts through educational interventions are therefore essential to foster students’ awareness and understanding of respectful and positive social interactions. This community service program aimed to increase students’ knowledge and awareness regarding bullying prevention at MI At-Taqwa, Gandasoli Village, Tanjung Siang District, Subang Regency. The program employed a Participatory Action Research (PAR) approach consisting of observation, planning, implementation, and evaluation stages. Educational activities were conducted through interactive lectures, discussions, educational video screenings, question-and-answer sessions, and role-playing exercises designed to help students identify bullying behaviors and appropriate responses. The results showed a significant improvement in students’ understanding of the forms, causes, and impacts of bullying, as well as strategies for preventing bullying in the school environment. Students demonstrated increased empathy, mutual respect, and willingness to create positive peer relationships. The active participation of teachers and students also contributed to the effectiveness of the program. This activity concludes that bullying prevention socialization is an effective educational strategy to strengthen anti-bullying awareness and support the development of a safe, inclusive, and supportive school environment.